AGRO-ENVIRONMENTAL JUSTIFICATION OF FERTILIZERS FOR WINTER WHEAT OF THE VARIETY "MYRONIVSKA 61" ON MEADOW-CHERN-EARTH SOIL OF THE NORTHERN PART OF THE NORTHERN PART OF THE FOREST STEPPE OF UKRAINE - Кудрявицька, Аліна (SWorldJournal, 2022)
Studies on meadow-chernozem carbonate soil have shown that long-term use of mineral fertilizers against the background of organic aftereffects, provides an increase in grain yield of the regional variety of winter wheat Myronivska 61 by 26.3 c / ha. Yield